2009
DOI: 10.1080/00926230802716336
|View full text |Cite
|
Sign up to set email alerts
|

Psychologists' Continuing Education and Training in Sexuality

Abstract: The current study explored whether psychologists are receiving continuing education that may assist them in providing intervention to clients with sexual issues. One hundred and five clinical and counseling psychologists completed an Internet survey. Results suggest that observational opportunities are underutilized and that more training related to sexual problems, as opposed to healthy sexuality, appears to be occurring. Participants with more continuing education were more likely to directly ask about and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 17 publications
7
38
0
Order By: Relevance
“…Like for other forms of self-efficacy (Bandura, 1997), education is one means to enhancing sexual intervention self-efficacy, at least regarding the ability to utilize sex therapy techniques and relay accurate sexual information. The overall low levels of sexual intervention selfefficacy of participants and the limited extent to which they were addressing their clients' sexual concerns suggest that psychologists (and likely clinicians from other professional groups) need more sexuality training both at the graduate level and through continuing education (Miller & Byers, 2009. Such training needs to increase sexual knowledge in general as well as to enhance skills related to efficacious treatment of a variety of common sexual issues and concerns.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Like for other forms of self-efficacy (Bandura, 1997), education is one means to enhancing sexual intervention self-efficacy, at least regarding the ability to utilize sex therapy techniques and relay accurate sexual information. The overall low levels of sexual intervention selfefficacy of participants and the limited extent to which they were addressing their clients' sexual concerns suggest that psychologists (and likely clinicians from other professional groups) need more sexuality training both at the graduate level and through continuing education (Miller & Byers, 2009. Such training needs to increase sexual knowledge in general as well as to enhance skills related to efficacious treatment of a variety of common sexual issues and concerns.…”
Section: Discussionmentioning
confidence: 90%
“…That is, many individuals will not discuss sexual issues unless the clinician initiates the conversation and demonstrates an openness and comfort with this topic even though their sexual concerns are relevant to the therapeutic goals (Hegarty, Brown, & Gunn, 2007;Metz & Seifert, 1990;Rubin,2004). Reissing and Di Giulio (2010; see also Miller & Byers, 2009) found that over half of the clinical psychologists they surveyed rarely or never asked clients about their sexual well-being. To be effective at developing strategies to enhance the likelihood that clinicians will address sexual concerns with their clients, it is important to identify factors that influence their willingness to do so.…”
Section: Introductionmentioning
confidence: 95%
“…This suggests that the workshop was instrumental in shifting clinicians' attitudes about the importance of sexual health in the lives of their patients. This goal has been noted as essential to improving treatment for women suffering from sexual complaints (Hinchliff, Gott, and Galena 2005;Miller and Byers 2009).…”
Section: Discussionmentioning
confidence: 98%
“…CE workshops are the major source of professional training after graduate school and healthcare professionals rate their CE experiences nearly as highly as their personal and clinical experience (Houge 1988). Miller and Byers (2009) report that psychologists who attend CE workshops focused on treating sexual complaints reported improved knowledge and greater feelings of competency and confidence. In addition, healthcare professionals who received CE training on sexual health issues were more likely to ask their patients about their sexual health, take a sexual history and treat sexual complaints (Houge 1988).…”
Section: Introductionmentioning
confidence: 95%
“…This behavior was pointed out by the lack of knowledge and attitude related to the elderly patient's sexual expression regardless of the health professionals' prejudices and age [7,8]. For the clinical nurses' taking a role as an educator with relation to sexual health with holistic and whole life cyclic view point, there is a necessity to confirm the human responses related to sexuality and to intervene it with enough knowledge of and adequate attitude toward sexuality of the elderly.…”
Section: Introductionmentioning
confidence: 99%